Before literature : the nature of narrative without the written word - Nayar, Sheila J. (Abingdon, Oxon ; New York : Routledge, 2019)
"Before Literature examines storytelling when, due to historical, technological or socio-economic circumstance, a narrative was neither shaped nor influenced by alphabetic literacy. How does a story unfold when carried solely in memory, when it could not be written down or externally stored? What structural and stylistic pressures were imposed when it had to travel through space and time exclusively by word of mouth? In Before Literature, Sheila J. Nayar addresses these very questions, guiding the reader in a lively and accessible manner through the key features of the storytelling that came before writing, print and digital communication. Nayar shows how narratives unaffected by these technologies, such as the Mahabharata and Homer's Odyssey, informed contemporary forms like Bollywood masala films, Hollywood spectaculars, comic books and beach reading. This clear and accessible guide is an ideal starting point for undergraduates approaching the study of orality. It offers a fundamentally different way of thinking about narrative, but also meaningfully and intelligibly discloses the "what" and "why" of literature, leading to a much deeper overall understanding and appreciation of its significance"--
Denaturalizing Literacy -- The Story Behind Before Literature -- Existence Without Inscription -- Myth and the Mythical, Epic and the Epical -- Why Pre-Lit Matters -- But There Is Always a But... -- A Beginning with No Definitive Beginning -- A Digression on the "Once Upon a Time..." of Star Wars -- Beginning In Medias Res -- Ending Anti-In Medias Res-and Pro-Status Quo -- "And This Happened... And Then This... And Then..." -- Epic Examples of Episodic Epics -- [[Boxes] within Boxes] within Boxes -- Flashbacks, Masala Style -- Lists, Lists, and More Lists -- In Defense of Clichés and the Formulaic (Yes, Really!) -- Repeat, Recycle-and Repeat (& Recycle) -- Whence the "Traditional"? -- The Acoustic Landscape -- Ancestors & Alienation -- Alienation & Participation -- The Agon of Audiences-But, Even More, of Actors -- Blood and Guts -- Violence + Veneration = A Polarized World -- When Exteriority Is Not a Bad Thing -- But, What of Art? What of Aesthetics? -- Oral Embodiment -- Superhuman Vessels -- Is Anti-Psychological Necessarily Unreal? -- Animating Abstract Knowledge -- Information Classification: General -- The Absence of Irony, the Pleasure of Parody -- Is There an Oral Chronosense? -- Do Intellectuals Suffer from Alphabetically Literate Elitism? -- Why the Humanities Matter-to All of Us.
OCLC-licensed vendor bibliographic record.
Keywords: Storytelling; Narration (Rhetoric); LITERARY COLLECTIONS / General; LITERARY CRITICISM / General